Analysis of the keeper-dependent strategy in the soccer penalty kick - Bowtell, M.; King, M.; Pain, M. (International Journal of Sports Science and Engineering, 2009)
The penalty kick plays a decisive role in the outcome of many Association Football (soccer) matches, and it is important for the kicker to choose the best strategy to score. This paper looked at the keeper-dependent strategy in which the kicker reacts to the goalkeeper`s movement, and determined the amount of time needed before foot-ball contact for a player to successfully adjust their kicking direction. Field tests were conducted with 8 participants using lights to simulate the time and direction of a keeper`s dive. A second experiment involving 6 participants determined simple, choice and discriminative reaction times for leg movements. It was found that the critical time needed to react and shoot the ball to the opposite side of the keeper was approximately 0.3 seconds. For three different strategies, involving different initial shooting directions, chance performance was found when stimuli were presented 300-400 ms before contact and full success rate was achieved when more than 500 ms were available. There were no significant differences between the strategies with regard to success. A large part of the pre-contact time was needed for reacting to the stimulus, and the time in which the adjustment could be made was approximately 135 ms.